In the previous section, we saw that scalar product of vectors obeys distributive law. In this section, we will see a practical application of the distributive law. We will also see a few more properties of the scalar product.
We will write the steps:
1. Consider the scalar product →A.→B
2. Let the rectangular components of →B be BxˆiandByˆj
3. Then we can write: →A.→B=→A.[Bxˆi+Byˆj]
• Applying distributive law, we get: →A.→B=→A.(Bxˆi)+→A.(Byˆj)
4. Now, let the rectangular components of →A be AxˆiandAyˆj
• Then the result in (3) becomes: →A.→B=[Axˆi+Ayˆj].(Bxˆi)+[Axˆi+Ayˆj].(Byˆj)
5. Applying distributive law, we get:
→A.→B=(Axˆi.Bxˆi)+(Ayˆj.Bxˆi)+(Axˆi.Byˆj)+(Ayˆj.Byˆj)
6. There are 4 terms on the right side. We will analyse each of them separately.
First term is (Axˆi.Bxˆi)
• This is a dot product of two vectors AxˆiandBxˆi
• To calculate the dot product, we want three items:
(i) The magnitude of the first vector
• In this case, it is Ax
(ii) The magnitude of the second vector
• In this case, it is Bx
(iii) Cosine of the angle θ between the two vectors
• In this case, both the vectors lie along the x axis. That means they are parallel
• The angle θ between them will be 0
• So cos θ = cos 0 = 1
■ Thus we get: (Axˆi.Bxˆi)=Ax×Bx×cos0=Ax×Bx×1=Ax×Bx
Second term is (Ayˆj.Bxˆi)
• This is a dot product of two vectors AyˆjandBxˆi
• To calculate the dot product, we want three items:
(i) The magnitude of the first vector
• In this case, it is Ay
(ii) The magnitude of the second vector
• In this case, it is Bx
(iii) Cosine of the angle θ between the two vectors
• In this case, the first vector lies along the y axis and the second vector lies along the x axis. That means they are perpendicular
• The angle θ between them will be 90o
• So cos θ = cos 90 = 0
(This is obvious because, we cannot project a vector onto another perpendicular vector)
■ Thus we get: (Ayˆj.Bxˆi)=Ay×Bx×cos90=Ay×Bx×0=0
Third term is (Axˆi.Byˆj)
• This is a dot product of two vectors AxˆiandByˆj
• To calculate the dot product, we want three items:
(i) The magnitude of the first vector
• In this case, it is Ax
(ii) The magnitude of the second vector
• In this case, it is By
(iii) Cosine of the angle θ between the two vectors
• In this case, the first vector lies along the x axis and the second vector lies along the y axis. That means they are perpendicular
• The angle θ between them will be 90o
• So cos θ = cos 90 = 0
(This is obvious because, we cannot project a vector onto another perpendicular vector)
■ Thus we get: (Axˆi.Byˆj)=Ax×By×cos90=Ax×By×0=0
Fourth term is (Ayˆj.Byˆj)
• This is a dot product of two vectors AyˆjandByˆj
• To calculate the dot product, we want three items:
(i) The magnitude of the first vector
• In this case, it is Ay
(ii) The magnitude of the second vector
• In this case, it is By
(iii) Cosine of the angle θ between the two vectors
• In this case, both the vectors lie along the y axis. That means they are parallel
• The angle θ between them will be 0
• So cos θ = cos 0 = 1
■ Thus we get: (Ayˆj.Byˆj)=Ay×By×cos0=Ay×By×1=Ay×By
7. Out of the four terms, the second and third terms become zero. So the final result is:
→A.→B=(Axˆi.Bxˆi)+(Ayˆj.Byˆj)
That is: →A.→B=AxBx+AyBy
■ We will write it as a result for easy reference
Eq.6.5:
If→A=Axˆi+Ayˆj
And→B=Bxˆi+Byˆj
Then→A.→B=AxBx+AyBy
8. From the above steps, we get two important results:
(i) The scalar product of two parallel vectors is simply the product of their magnitudes
• This is clear from the analysis of first and fourth terms
(ii) The scalar product of two perpendicular vectors is zero
• This is clear from the analysis of second and third terms
■ We will write them as results for easy reference
Eq.6.6:
If→Aand→Bare parallel
Then→A.→B=|→A|×|→B|
Eq.6.7:
If→Aand→Bare perpendicular
Then→A.→B=0
9. The result in (7) can be extended to three dimensions also. We get:
Eq.6.8:
If→A=Axˆi+Ayˆj+Azˆk
And→B=Bxˆi+Byˆj+Bzˆk
Then→A.→B=AxBx+AyBy+AzBz
Just as we calculated →A.→B above, we can calculate →A.→A also
We will write the steps:
1. Consider the scalar product →A.→A
2. Let the rectangular components of →A be AxˆiandAyˆj
3. Then we can write: →A.→A=→A.[Axˆi+Ayˆj]
Applying distributive law, we get: →A.→A=→A.(Axˆi)+→A.(Ayˆj)
4. Now, split the other →A also
Then the result in (3) becomes: →A.→A=[Axˆi+Ayˆj].(Axˆi)+[Axˆi+Ayˆj].(Ayˆj)
5. Applying distributive law, we get:
→A.→A=(Axˆi.Axˆi)+(Ayˆj.Axˆi)+(Axˆi.Ayˆj)+(Ayˆj.Ayˆj)
6. There are 4 terms on the right side
• Each term is a dot product of two vectors
• If the two vectors in a term are perpendicular to each other, that term will become zero
• Thus the second and third terms will become zero
7. So the final result is:
→A.→A=(Axˆi.Axˆi)+(Ayˆj.Ayˆj)
That is: →A.→A=AxAx+AyAy
That is: →A.→A=A2x+A2y
■ We will write it as a result for easy reference
Eq.6.9:
If→A=Axˆi+Ayˆj
Then→A.→A=A2x+A2y
8. The result in (7) can be extended to three dimensions also. We get:
→A.→A=(Axˆi+Ayˆj+Azˆk).(Axˆi+Ayˆj+Azˆk)=A2x+A2y+A2z
■ We will write it as a result for easy reference
Eq.6.10:
If→A=Axˆi+Ayˆj+Azˆk
Then→A.→A=A2x+A2y+A2z
Next we will prove that, if →B=Bxˆi+Byˆj,
Then: λ→B=λ(Bxˆi+Byˆj)=(λBx)ˆi+(λBy)ˆj
Where λ is a scalar quantity
• A graphic representation of this property is shown in fig.6.5 below:
• BxˆiandByˆj are the rectangular components of →B
• Bxˆi is multiplied by a scalar λ
♦ This gives a new vector
• Byˆj is multiplied by the same scalar λ
♦ This gives another new vector
• There will be a resultant for these two new vectors
• This new resultant is →B multiplied by λ
■ That means:
♦ The magnitude of the new resultant is: λ|→B|
♦ The direction of the new resultant is same as that of →B
We will write the steps to prove it:
1. On the left side, we are multiplying a vector by a scalar λ
• Then the magnitude of the new vector will become λ|→B|
• The direction of the new vector will be same as the original
• We have to arrive at the above results from the right side also. Let us try:
2. On the right side, we have a vector: (λBx)ˆi+(λBy)ˆj
• The magnitude of this vector will be: √(λBx)2+(λBy)2=√λ2B2x+λ2B2y (Using Eq.4.2)
=√λ2(B2x+B2y)=λ√(B2x+B2y)=λ|→B|
• So magnitude of (λBx)ˆi+(λBy)ˆj is same as the magnitude of λ→B
3. The direction of (λBx)ˆi+(λBy)ˆj is given by:
θ=tan−1λByλBx=tan−1ByBx
• So direction of (λBx)ˆi+(λBy)ˆj is same as the direction of λ→B
■Thus we proved that: λ→B=λ(Bxˆi+Byˆj)=(λBx)ˆi+(λBy)ˆj
■ We will write it as a result for easy reference
Eq.6.11:
If→B=Bxˆi+Byˆj
Thenλ→B=(λBx)ˆi+(λBy)ˆj
We will write the steps:
1. First we will work on the left side
λ→B=(λBx)ˆi+(λBy)ˆj
[Using Eq.6.11]
• Now, multiplying both sides by →A, we get:
→A.(λ→B)=→A[(λBx)ˆi+(λBy)ˆj]
• Applying distributive law, we get:
→A.(λ→B)=→A.[(λBx)ˆi]+→A.[(λBy)ˆj]
• Now we put →A=(Axˆi+Ayˆj). We get:
→A.(λ→B)=(Axˆi+Ayˆj).[(λBx)ˆi]+(Axˆi+Ayˆj).[(λBy)ˆj]
• Applying distributive law, we get:
→A.(λ→B)=Axˆi.[(λBx)ˆi]+Ayˆj.[(λBx)ˆi]+Axˆi.[(λBy)ˆj]+Ayˆj.[(λBy)ˆj]
2. There are 4 terms in the above result
• Each term is a dot product of two vectors
• If the two vectors in a term are perpendicular to each other, that term will become zero
• Thus the second and third terms will become zero
• We get: →A.(λ→B)=Axˆi.[(λBx)ˆi]+Ayˆj.[(λBy)ˆj]
=Ax(λBx)+Ay(λBy)
=λAxBx+λAyBy
3. Now we work on the right side
• On the right side, we have λ(→A.→B)
• But using Eq6.5, →A.→B=AxBx+AyBy
• So the right side becomes: λ(→A.→B)=λ(AxBx+AyBy)=λAxBx+λAyBy
• This is same as the result in (2)
• So L.H.S = R.H.S
• Thus we proved that →A.(λ→B)=λ(→A.→B)
■ We will write it as a result for easy reference
Eq.6.12:
→A.(λ→B)=λ(→A.→B)
We will write the steps:
1. Consider the scalar product →A.→B
2. Let the rectangular components of →B be BxˆiandByˆj
3. Then we can write: →A.→B=→A.[Bxˆi+Byˆj]
• Applying distributive law, we get: →A.→B=→A.(Bxˆi)+→A.(Byˆj)
4. Now, let the rectangular components of →A be AxˆiandAyˆj
• Then the result in (3) becomes: →A.→B=[Axˆi+Ayˆj].(Bxˆi)+[Axˆi+Ayˆj].(Byˆj)
5. Applying distributive law, we get:
→A.→B=(Axˆi.Bxˆi)+(Ayˆj.Bxˆi)+(Axˆi.Byˆj)+(Ayˆj.Byˆj)
6. There are 4 terms on the right side. We will analyse each of them separately.
First term is (Axˆi.Bxˆi)
• This is a dot product of two vectors AxˆiandBxˆi
• To calculate the dot product, we want three items:
(i) The magnitude of the first vector
• In this case, it is Ax
(ii) The magnitude of the second vector
• In this case, it is Bx
(iii) Cosine of the angle θ between the two vectors
• In this case, both the vectors lie along the x axis. That means they are parallel
• The angle θ between them will be 0
• So cos θ = cos 0 = 1
■ Thus we get: (Axˆi.Bxˆi)=Ax×Bx×cos0=Ax×Bx×1=Ax×Bx
Second term is (Ayˆj.Bxˆi)
• This is a dot product of two vectors AyˆjandBxˆi
• To calculate the dot product, we want three items:
(i) The magnitude of the first vector
• In this case, it is Ay
(ii) The magnitude of the second vector
• In this case, it is Bx
(iii) Cosine of the angle θ between the two vectors
• In this case, the first vector lies along the y axis and the second vector lies along the x axis. That means they are perpendicular
• The angle θ between them will be 90o
• So cos θ = cos 90 = 0
(This is obvious because, we cannot project a vector onto another perpendicular vector)
■ Thus we get: (Ayˆj.Bxˆi)=Ay×Bx×cos90=Ay×Bx×0=0
Third term is (Axˆi.Byˆj)
• This is a dot product of two vectors AxˆiandByˆj
• To calculate the dot product, we want three items:
(i) The magnitude of the first vector
• In this case, it is Ax
(ii) The magnitude of the second vector
• In this case, it is By
(iii) Cosine of the angle θ between the two vectors
• In this case, the first vector lies along the x axis and the second vector lies along the y axis. That means they are perpendicular
• The angle θ between them will be 90o
• So cos θ = cos 90 = 0
(This is obvious because, we cannot project a vector onto another perpendicular vector)
■ Thus we get: (Axˆi.Byˆj)=Ax×By×cos90=Ax×By×0=0
Fourth term is (Ayˆj.Byˆj)
• This is a dot product of two vectors AyˆjandByˆj
• To calculate the dot product, we want three items:
(i) The magnitude of the first vector
• In this case, it is Ay
(ii) The magnitude of the second vector
• In this case, it is By
(iii) Cosine of the angle θ between the two vectors
• In this case, both the vectors lie along the y axis. That means they are parallel
• The angle θ between them will be 0
• So cos θ = cos 0 = 1
■ Thus we get: (Ayˆj.Byˆj)=Ay×By×cos0=Ay×By×1=Ay×By
7. Out of the four terms, the second and third terms become zero. So the final result is:
→A.→B=(Axˆi.Bxˆi)+(Ayˆj.Byˆj)
That is: →A.→B=AxBx+AyBy
■ We will write it as a result for easy reference
Eq.6.5:
If→A=Axˆi+Ayˆj
And→B=Bxˆi+Byˆj
Then→A.→B=AxBx+AyBy
8. From the above steps, we get two important results:
(i) The scalar product of two parallel vectors is simply the product of their magnitudes
• This is clear from the analysis of first and fourth terms
(ii) The scalar product of two perpendicular vectors is zero
• This is clear from the analysis of second and third terms
■ We will write them as results for easy reference
Eq.6.6:
If→Aand→Bare parallel
Then→A.→B=|→A|×|→B|
Eq.6.7:
If→Aand→Bare perpendicular
Then→A.→B=0
9. The result in (7) can be extended to three dimensions also. We get:
Eq.6.8:
If→A=Axˆi+Ayˆj+Azˆk
And→B=Bxˆi+Byˆj+Bzˆk
Then→A.→B=AxBx+AyBy+AzBz
Just as we calculated →A.→B above, we can calculate →A.→A also
We will write the steps:
1. Consider the scalar product →A.→A
2. Let the rectangular components of →A be AxˆiandAyˆj
3. Then we can write: →A.→A=→A.[Axˆi+Ayˆj]
Applying distributive law, we get: →A.→A=→A.(Axˆi)+→A.(Ayˆj)
4. Now, split the other →A also
Then the result in (3) becomes: →A.→A=[Axˆi+Ayˆj].(Axˆi)+[Axˆi+Ayˆj].(Ayˆj)
5. Applying distributive law, we get:
→A.→A=(Axˆi.Axˆi)+(Ayˆj.Axˆi)+(Axˆi.Ayˆj)+(Ayˆj.Ayˆj)
6. There are 4 terms on the right side
• Each term is a dot product of two vectors
• If the two vectors in a term are perpendicular to each other, that term will become zero
• Thus the second and third terms will become zero
7. So the final result is:
→A.→A=(Axˆi.Axˆi)+(Ayˆj.Ayˆj)
That is: →A.→A=AxAx+AyAy
That is: →A.→A=A2x+A2y
■ We will write it as a result for easy reference
Eq.6.9:
If→A=Axˆi+Ayˆj
Then→A.→A=A2x+A2y
8. The result in (7) can be extended to three dimensions also. We get:
→A.→A=(Axˆi+Ayˆj+Azˆk).(Axˆi+Ayˆj+Azˆk)=A2x+A2y+A2z
■ We will write it as a result for easy reference
Eq.6.10:
If→A=Axˆi+Ayˆj+Azˆk
Then→A.→A=A2x+A2y+A2z
Next we will prove that, if →B=Bxˆi+Byˆj,
Then: λ→B=λ(Bxˆi+Byˆj)=(λBx)ˆi+(λBy)ˆj
Where λ is a scalar quantity
• A graphic representation of this property is shown in fig.6.5 below:
![]() |
Fig.6.5 |
• Bxˆi is multiplied by a scalar λ
♦ This gives a new vector
• Byˆj is multiplied by the same scalar λ
♦ This gives another new vector
• There will be a resultant for these two new vectors
• This new resultant is →B multiplied by λ
■ That means:
♦ The magnitude of the new resultant is: λ|→B|
♦ The direction of the new resultant is same as that of →B
We will write the steps to prove it:
1. On the left side, we are multiplying a vector by a scalar λ
• Then the magnitude of the new vector will become λ|→B|
• The direction of the new vector will be same as the original
• We have to arrive at the above results from the right side also. Let us try:
2. On the right side, we have a vector: (λBx)ˆi+(λBy)ˆj
• The magnitude of this vector will be: √(λBx)2+(λBy)2=√λ2B2x+λ2B2y (Using Eq.4.2)
=√λ2(B2x+B2y)=λ√(B2x+B2y)=λ|→B|
• So magnitude of (λBx)ˆi+(λBy)ˆj is same as the magnitude of λ→B
3. The direction of (λBx)ˆi+(λBy)ˆj is given by:
θ=tan−1λByλBx=tan−1ByBx
• So direction of (λBx)ˆi+(λBy)ˆj is same as the direction of λ→B
■Thus we proved that: λ→B=λ(Bxˆi+Byˆj)=(λBx)ˆi+(λBy)ˆj
■ We will write it as a result for easy reference
Eq.6.11:
If→B=Bxˆi+Byˆj
Thenλ→B=(λBx)ˆi+(λBy)ˆj
Next we will prove that →A.(λ→B)=λ(→A.→B)
1. First we will work on the left side
λ→B=(λBx)ˆi+(λBy)ˆj
[Using Eq.6.11]
• Now, multiplying both sides by →A, we get:
→A.(λ→B)=→A[(λBx)ˆi+(λBy)ˆj]
• Applying distributive law, we get:
→A.(λ→B)=→A.[(λBx)ˆi]+→A.[(λBy)ˆj]
• Now we put →A=(Axˆi+Ayˆj). We get:
→A.(λ→B)=(Axˆi+Ayˆj).[(λBx)ˆi]+(Axˆi+Ayˆj).[(λBy)ˆj]
• Applying distributive law, we get:
→A.(λ→B)=Axˆi.[(λBx)ˆi]+Ayˆj.[(λBx)ˆi]+Axˆi.[(λBy)ˆj]+Ayˆj.[(λBy)ˆj]
2. There are 4 terms in the above result
• Each term is a dot product of two vectors
• If the two vectors in a term are perpendicular to each other, that term will become zero
• Thus the second and third terms will become zero
• We get: →A.(λ→B)=Axˆi.[(λBx)ˆi]+Ayˆj.[(λBy)ˆj]
=Ax(λBx)+Ay(λBy)
=λAxBx+λAyBy
3. Now we work on the right side
• On the right side, we have λ(→A.→B)
• But using Eq6.5, →A.→B=AxBx+AyBy
• So the right side becomes: λ(→A.→B)=λ(AxBx+AyBy)=λAxBx+λAyBy
• This is same as the result in (2)
• So L.H.S = R.H.S
• Thus we proved that →A.(λ→B)=λ(→A.→B)
■ We will write it as a result for easy reference
Eq.6.12:
→A.(λ→B)=λ(→A.→B)
No comments:
Post a Comment